A Gluteus-Specific Muscle Synergy Recruited During the First Recovery Step Following a Backward Pitch Perturbation - Huijie Lin; Xiping Ren; Christoph Lutter; Haidan Liang; Fengxue Qi; Qining Yang; Maeruan Kebbach; Martin Schlegel; Sven Bruhn; Rainer Bader; Thomas Tischer (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
The central nervous system momentarily activates a set of specific muscle synergies to maintain balance when external mechanical perturbations induce walking instability, which is critically involved in preventing falls. The activation patterns and composition of the muscle synergies recruited in the perturbed leg have not been fully characterized, and even less so for the recovery step. Here, we addressed this research gap by measuring the surface electromyographic data of the relevant muscles during a backward-pitched perturbed walk, and then extracting muscle synergy-related parameters using a non-negative matrix factorization algorithm. Our findings indicated that 1) a common set of four muscle synergies was activated in normal, perturbated and first recovery steps; 2) a specific muscle synergy controlled hip movement was recruited in the first recovery step; and 3) the main temporal activation phases of several muscle synergies were prolonged in the perturbed or the first recovery step. These results emphasize the potential significance of exploring the neurological control strategies of muscle synergy in fall prevention.